Separation of perfluoroalkyl substances by using nonaqueous capillary electrophoresis with conductivity detection. Issue 7 (4th May 2020) - Lees, Heidi; Jõul, Piia; Siilak, Kristjan; Vaher, Merike
Abstract: Perfluoroalkyl substances are chemical pollutants whose levels in the environment should be monitored. This work implemented nonaqueous capillary electrophoresis with conductivity detection to achieve separation of perfluoroheptanoic acid, perfluorooctanoic acid, and perfluorooctanesulfonate within 5 min. The mixture of 3‐( N ‐morpholino)propanesulfonic acid and triethylamine in acetonitrile/methanol (50:50, v/v) was used as a background electrolyte. The method was linear (coefficients of determination ˃ 0.996) at analyte concentrations ranging from 2 to 20 μM with instrument detection limits varying between 0.30 and 0.75 μM depending on the analyte. The developed method was precise, the relative standard deviation of repeatability ( n  = 6) and reproducibility ( n  = 5) were less than 5.8% for the analytes used. The method was applied to the analysis of perfluoroheptanoic acid, perfluorooctanoic acid, and perfluorooctanesulfonate in wastewater samples treated by solid‐phase extraction, which further made it possible to achieve the method detection limits of perfluoroalkyl substances as low as 0.1–0.4 nM. Additionally, the applicability of the novel carbon aerogel‐based solid‐phase extraction and magnetic solid‐phase extraction were tested for the extraction of target compounds. It would be possible to transform the developed method into a portable format for on‐site analysis.